Analisis Daya Saing dan Faktor yang Mempengaruhi Volume Ekspor Biji Kopi Indonesia Ke Jepang - Cindi Novariani; Muchtolifah Muchtolifah; Sishadiyati Sishadiyati (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Indonesia is one of the developing countries in the world with abundant availability of natural resources, one of which is coffee bean commodities. Overproduction will be a benefit if the commodity can be exported mainly to developed countries, one of which is Japan. This study aims to analyze how much competitiveness value of Indonesian coffee bean commodities and factors that affect the volume of Indonesian coffee bean exports to Japan. This study used secondary data with a period of 12 years in the period 2008-2019. The Revealed Comparative Advantage (RCA) method is used to analyze the competitiveness of coffee beans as well as the Double Linear Regression Analysis with the Ordinary Least Square (OLS) model used to analyze the influence of coffee bean production, exchange rates and international prices of coffee on the volume of coffee bean exports to Japan. The results of the study found that during the period 2008-2019 the value of Indonesian coffee beans RCA  has a strong competitiveness because it has a value of more than 1; partial production of coffee beans does not affect the export volume of coffee beans while the exchange rate and international price of coffee partially negatively affects the volume of Indonesian coffee beans exports to Japan.